EFFECT OF REGIONAL TAX, REGIONAL RETRIBUTION, GENERAL ALLOCATION FUNDS AND SPECIAL ALLOCATION FUNDS ON LOCAL GOVERNMENT CAPITAL GOODS IN CENTRAL JAVA AND REGIONAL REGION IN YOGYAKARTA IN 2016 - Retno Sri Widyastuti (STIE AUB Surakarta, 2018)
The purpose of this study is to analyze and provide empirical evidence of the effect that local taxes, levies, DAU, and DAK on regional government capital spending in Central Java and Yogyakarta. The population of this study is the regional government of Central Java and Yogyakarta in 2016. The sample chosen to be the object of this study is the regional government of Central Java and Yogyakarta in 2016 a number of 40 cities / districts. The sampling technique in this study is the census that takes the entire number of existing population. The method of analysis in this study consisted of classical assumption test, multiple linear regression analysis, t test, and R2 test. The results of the classical assumption test show that all variables have a normal distribution, free from multicollinearity, does not contain any heterokedastisitas and there is no autocorrelation. The results of hypothesis testing show that local taxes have a positive and significant impact on regional government capital spending in Central Java and Yogyakarta, Levy area has a positive but not significant impact on regional government capital expenditure in Central Java and Yogyakarta, DAU has a positive and significant impact on regional government capital spending in Central Java and DIY, and DAK have positive but not significant influence to regional government capital expenditure in Central Java and Yogyakarta. Result of test of R2 (coefficient of determination) is known that local tax, regional retribution, DAU, and DAK able to explain equal to 52,7% to variable of Local Government capital expenditure in Central Java and DIY, while the rest equal to 47,3% explained by other variable like income others, non-tax proceeds, and tax-deductible funds. Keywords: capital expenditure, regional tax, regional retribution, DAU, and DAK